Avances clínicos y terapéuticos en los últimos 10 años en la neumonía adquirida en la comunidad de adultos. - Jordan Freire, Dayanna Fernanda (2023)
The main objective of this research study was to focus on the clinical and therapeutic management of Community-Acquired Pneumonia (CAP) which has undergone significant advances in the last decades, with a better understanding of the associated risk factors, which implies considering the specific characteristics of the disease and particular characteristics of each patient, such as age, comorbidities, immunological status, identification of the infectious agent, severity of the disease, response to previous treatments, prognosis, epidemiology of the disease and appropriate choice of drug therapy. In addition, emphasis has been given to the optimization of antibiotic therapy, taking into account bacterial resistance and the correct choice of antibiotics. Therefore, the effective implementation of current trends in the clinical and therapeutic management of CAP requires constant updating of healthcare professionals and their participation in continuing education programs, in order to keep abreast of the latest evidence and recommendations and to apply them appropriately in clinical practice. In order to explore this topic in more depth, a multidisciplinary research study was proposed, developed under a descriptive study, with a non-experimental design and a bibliographic review. By the established inclusion and exclusion criteria, 59 scientific articles were selected to characterize the epidemiology and etiology, identify the effectiveness of the most recent diagnostic strategies, and systematize the current treatment guidelines for CAP in adults in the community. From the results, we conclude that CAP is a respiratory disease of high incidence and burden for health systems, so knowledge, understanding, and application of clinical and therapeutic management, with a multidisciplinary approach, including risk scales, is essential to ensure comprehensive and quality patient care.